MID-TO LATE-HOLOCENE RELATIVE SEA-LEVEL CHANGE IN SOUTHWEST BRITAIN AND THE INFLUENCE OF SEDIMENT COMPACTION - Edwards R.J. (My University, 2006)
Relative sea-level changes in southwest Britain are poorly constrained because of limitations in the quality and quantity of existing geological data. As a consequence, in contrast to most other regions in the UK, it is not possible to reliably infer rates of land and sea-level change during the last few thousand years. Furthermore, geologically based sea-level reconstructions from this area display significant misfits with relative sea-level predictions based on a recent global model of the glacio-isostatic adjustment process. This paper presents a new record of relative sea-level change for the last 4000 years derived from radiocarbon-dated sea-level index points. In addition to providing information concerning the pattern and rates of late Holocene sea-level change, these data are used to evaluate the suggestion that the apparent misfits between model predictions and geological reconstructions can be satisfactorily explained as a consequence of the lowering of sea-level index points by sediment compaction. The results indicate that a simple, first-order method of decompaction based on the stratigraphic position of sea-level index points, can eliminate much of the misfit between reconstructions and predictions, and substantially reduce vertical scatter in geological data. They also suggest that the influence of compaction on sea-level data from this region may be larger than previously thought. The simple addition of reliable stratigraphic data, in combination with targeted sampling, has the potential to improve our understanding of the compaction process, and increase the utility of existing data. This is increasingly important as the partnership between geophysical modelling and geological investigation becomes more commonplace in sea-level studies around the world.
Keywords: RELATIVE SEA LEVEL; SEDIMENT COMPACTION; GLACIO-ISOSTASY ADJUSTMENT; SOUTHWEST BRITAIN; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен